Selected residential mortgage loan risk factors and their impact on household stability in Poland - Willmann, Mariola (Wybrane czynniki ryzyka hipotecznych kredytów mieszkaniowych i ich wpływ na stabilność gospodarstw domowych w Polsce, 2011)
The article provides a brief presentation of the residential mortgage loan portfolio structure with a special focus on the portfolio’s quality and its potential fluctuations resulting from the materialization of the analyzed risk factors. The presentation will consider first and foremost to what extent selected risk factors related to residential mortgage loans influence stability and financial standing of households. For reasons of space, the following selected factors will be discussed in the paper: loan currency, LTV, FX rates fluctuations and the term of the loan. Theoretical discussion has been illustrated by several figures and tables
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 208-222
Keywords: residential loans; credit risk; fx risk; interest rate risk; financial standing of households